Systematic review of randomized controlled trials in the treatment of dry eye disease in Sjogren syndrome - Shih, Kendrick Co (J Inflamm (Lond), 2017)
Primary Sjögren’s syndrome is an autoimmune disease characterized by dry eye and dry mouth. We systematically reviewed all the randomized controlled clinical trials published in the last 15 years that included ocular outcomes. We found 22 trials involving 9 topical, 10 oral, 2 intravenous and 1 subcutaneous modalities of treatment. Fluoromethalone eye drops over 8 weeks were more effective than topical cyclosporine in the treatment of dry eye symptoms and signs; similarly, indomethacin eye drops over 1 month were more efficacious than diclofenac eye drops. Oral pilocarpine 5 mg twice daily over 3 months was superior to use of lubricants or punctal plugs for treating dry eye, but 5% of participants had gastrointestinal adverse effects from pilocarpine, though none discontinued treatment. In contrast, etanercept, a TNF-alpha blocking antibody, administered as subcutaneous injections twice weekly, did not improve dry eye significantly compared to placebo injections. In conclusion, topical corticosteroids have been shown to be effective in dry eye associated with Sjögren’s syndrome. As some topical non-steroidal anti-inflammatory drugs may be more effective than others, these should be further evaluated. Systemic secretagogues like pilocarpine have a role in Sjögren’s syndrome but the adverse effects may limit their clinical use. It is disappointing that systemic cytokine therapy did not produce encouraging ocular outcomes but participants should have assessment of cytokine levels in such trials, as those with higher baseline cytokine levels may respond better. (229 words)